Encapsulation of magnetic nanoparticles into carbon nanotubes by one-step facile synthesis method - José D. Pizha; Diana G. Heredia; Luis Corredor; Carlos Reinoso; Werner Bramer; Jules Gardener; Guillermo Solorzano; Gema Gonzalez (Carbon Trends)
Magnetic carbon nanotubes (MagCNTs) have attracted significant interest due to their exceptional magnetic properties, robust adsorption capabilities, and unique thermal conductivity, making them valuable in fields such as drug delivery and environmental technology. However, their production and design face challenges due to complex methodologies and the exposure of magnetic nanoparticles (NPs) to the environment, which hinders scalability and compromises their applications. Issues like rapid oxidation of iron-based NPs and potential toxicity of alternative metals like cobalt or nickel further limit their efficacy and utility. To address these challenges, encapsulating the metallic NPs can preserve their magnetic properties and enhance application options. In this study, we introduce a novel, in-situ, one-step synthesis method to encapsulate magnetic NPs, such as Fe3O4, Fe, and Fe3C, within the structure of carbon nanotubes (CNTs). The material was synthesized via Chemical Vapor Deposition (CVD) using Fe3O4 NPs as the catalyst. The composition and morphology were studied using High Resolution Transmission Electron Microscopy (HRTEM), Energy Dispersive X-ray Spectroscopy (EDS), Raman spectroscopy, X-ray Diffraction (XRD), X-ray Photoelectron Spectroscopy (XPS), Thermogravimetric Analysis (TGA), and vibrating sample magnetometry (VSM). These analysis revealed the effective confinement of magnetic NPs, with size approximately 10–20 nm, within the CNTs. Furthermore, VSM results confirmed the magnetic properties at room temperature, with a magnetic saturation value of 35.8 emu/g. This approach offers a refined production process and material design, expanding their applicability in various technological and biomedical fields.